Reimagining Bolivian cuisine: Haute traditional food and its discontents. Issue 4 (2nd October 2019) - Sammells, Clare A.
Abstract: This article considers the emerging Bolivian gastronomic discourse as a project fraught with tensions. On the one hand, the discourse surrounding Bolivian cuisine, as presented in urban restaurants, highlights a new kind of nationalism that promotes regional cooking and innovation. This process has elevated indigenous ingredients, such as quinoa, chuño (freeze-dried potatoes), and llama meat, to the status of delicacies. This gastronomic emergence parallels the recent rise of an indigenous middle-class, as well as the shifting political boundaries between indigenous and non-indigenous in the era of President Evo Morales. Nevertheless, elite urban forms of Bolivian cuisine only partially transcend gender, class, and ethnic divides; they sometimes have the (unintended) effect of highlighting and re-inscribing existing social fault-lines. This article considers how indigenous Bolivian women are used to mark Bolivian cuisine, while they are simultaneously marginalized from it. While indigenous women dominate the "culinary field" of quotidian eating in domestic and marketplace arenas, they are far less evident in the "gastronomic fields" of elite restaurants, cookbooks, and written texts. Despite this exclusion, their presence is often invoked through ethnically-marked clothing such as the pollera and their symbolic production of "local" food.